ANALYSIS OF RESIDENTIAL AREA DEVELOPMENT IN KARO DISTRICT - Hendra Gunawan Halawa; Wahyu Hidayat; Feby Milanie (PT. Radja Intercontinental Publishing, 2024)
The development of a region is greatly influenced by the development of settlements to accommodate the population in the region. Settlement problems often occur due to lack of settlement development planning, resulting in a decline in the quality of settlements. Therefore, it is necessary to conduct an analysis of settlement development. This study was conducted in the scope of Karo Regency which aims to analyze potential land to be used as a settlement area in Karo Regency. The approach used in this study is descriptive qualitative using the superimpose analysis method (overlay) and SWOT analysis. The superimpose method is carried out by overlaying a physical map of the region, and areas that have the potential to be protected. So that it produces a direction for the potential development of the settlement area. The research results show that the limited area of 128,127.81 hectares can be pushed into protected areas and agricultural areas,The constraint area of 44,812.12 Ha is a constraint area that can be developed in a limited way as residential development, and the potential area of 45,791.61 Ha is a potential area that is highly recommended as land for built-up or residential development.